O PROCESSO DE NEGOCIAÇÃO E O ALCANCE DA COMPLETUDE MONOLÓGICA EM DEBATE ELEITORAL. - Ximenes Cunha, Gustavo (Trabalhos em Lingüística Aplicada)
In this paper, the objective is to study the constraints imposed by a contextual property of the electoral debate (namely, the partial and controlled reciprocity between the interlocutors) about the task of producing interventions that can be evaluated as complete. Adopting the Geneva Model of discourse analysis as theoretical framework and analyzing the last electoral debate of the presidential campaign that took place in 2014, a debate whose opponents were Dilma Rousseff (PT) and Aécio Neves (PSDB), we obtained the following results: i) in the intervention in which the candidates ask the question, it is anticipated by a functionally and structurally complex preparatory intervention; ii) reactive interventions (responses and replies) are formed by steps that are linked to information from the intervention previously produced by the opponent and/or audience member (voter) invited to ask; iii) in the construction of each reactive intervention, these steps can be coordinated or articulated by subordination; iv) in each of these steps, there may be discourse segments representing both the speech of the opponent and the speech of the audience member invited to ask.